2007
DOI: 10.1159/000109662
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Significance of the Six-Minute Walk Distance for Long-Term Survival in Chronic Hypercapnic Respiratory Failure

Abstract: Background: The 6-min walk distance (6-MWD) is a global marker of functional capacity and prognosis in chronic obstructive pulmonary disease (COPD), but less explored in other chronic respiratory diseases. Objective: To study the role of 6-MWD in chronic hypercapnic respiratory failure (CHRF). Methods: In 424 stable patients with CHRF and non-invasive ventilation (NIV) comprising COPD (n = 197), restrictive diseases (RD; n = 112) and obesity-hypoventilation-syndrome (OHS; n = 115), the prognostic value of 6-MW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 85 publications
(74 reference statements)
1
20
0
2
Order By: Relevance
“…The authors calculated the percent-of-predicted 6MWD, but they did not use them for analysis. 7 In the present study, although the majority of the subjects had mildly less hypercapnic and hypoxemic ABG values and worse spirometry results, especially in OHS, they were more or less similar to the patients presented in the Budweiser report. Our study had higher 6MWD and predicted values.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…The authors calculated the percent-of-predicted 6MWD, but they did not use them for analysis. 7 In the present study, although the majority of the subjects had mildly less hypercapnic and hypoxemic ABG values and worse spirometry results, especially in OHS, they were more or less similar to the patients presented in the Budweiser report. Our study had higher 6MWD and predicted values.…”
Section: Discussionsupporting
confidence: 78%
“…[3][4][5][6] Actual 6MWD was also studied in chronic hypercapnic respiratory failure patients who were using home noninvasive ventilation (NIV). 7 Budweiser et al found a similar hazard ratio for mortality for the actual 6MWD and percent-of-predicted 6MWD in 424 patients with chronic hypercapnic respiratory failure using home NIV. 7 However, they did not study the relationship between pulmonary function and actual 6MWD versus percent-of-predicted 6MWD.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations